Placental Mammals Acquired Functional Sequences in NRK for Regulating the CK2–PTEN–AKT Pathway and Placental Cell Proliferation. (6th January 2022) - Lestari, Beni; Naito, Satomi; Endo, Akinori; Nishihara, Hidenori; Kato, Akira; Watanabe, Erika; Denda, Kimitoshi; Komada, Masayuki; Fukushima, Toshiaki
Abstract: The molecular evolution processes underlying the acquisition of the placenta in eutherian ancestors are not fully understood. Mouse NCK-interacting kinase (NIK)-related kinase (NRK) is expressed highly in the placenta and plays a role in preventing placental hyperplasia. Here, we show the molecular evolution of NRK, which confers its function for inhibiting placental cell proliferation. Comparative genome analysis identified NRK orthologs across vertebrates, which share the kinase and citron homology (CNH) domains. Evolutionary analysis revealed that NRK underwent extensive amino acid substitutions in the ancestor of placental mammals and has been since conserved. Biochemical analysis of mouse NRK revealed that the CNH domain binds to phospholipids, and a region in NRK binds to and inhibits casein kinase-2 (CK2), which we named the CK2-inhibitory region (CIR). Cell culture experiments suggest the following: 1) Mouse NRK is localized at the plasma membrane via the CNH domain, where the CIR inhibits CK2. 2) This mitigates CK2-dependent phosphorylation and inhibition of PTEN and 3) leads to the inhibition of AKT signaling and cell proliferation. Nrk deficiency increased phosphorylation levels of PTEN and AKT in mouse placenta, supporting our hypothesis. Unlike mouse NRK, chicken NRK did not bind to phospholipids and CK2, decrease phosphorylation of AKT, or inhibit cell proliferation. Both the CNH domain and CIR have evolved under purifying selection in placental mammals. Taken together, our study suggests that placental mammals acquired the phospholipid-binding CNH domain and CIR in NRK for regulating the CK2–PTEN–AKT pathway and placental cell proliferation.